Arabidopsis clathrin adaptor EPSIN1 but not MODIFIED TRANSPORT TO THE VACOULE1 contributes to effective plant immunity against pathogenic Pseudomonas bacteria. (31st December 2023) - Mason, Kelly; LaMontagne-Mueller, Erica; Sauer, Michael; Heese, Antje
ABSTRACT: In eukaryotes, EPSINs are Epsin N -terminal Homology (ENTH) domain-containing proteins that serve as monomeric clathrin adaptors at the plasma membrane (PM) or the trans- Golgi Network (TGN)/early endosomes (EE). The model plant Arabidopsis thaliana encodes for seven ENTH proteins, of which so far, only At EPSIN1 ( At EPS1) and MODIFIED TRANSPORT TO THE VACUOLE1 ( At MTV1) localize to the TGN/EE and contribute to cargo trafficking to both the cell surface and the vacuole. However, relatively little is known about role(s) of any plant EPSIN in governing physiological responses. We have recently shown that At EPS1 is a positive modulator of plant immune signaling and pattern-triggered immunity against flagellated Pseudomonas syringae pv. tomato ( Pto ) DC3000 bacteria. In eps1 mutants, impaired immune responses correlate with reduced accumulation of the receptor FLAGELLIN SENSING2 ( At FLS2) and the convergent immune co-receptor BRASSINOSTEROID INSENTIVE1-ASSOCIATED RECEPTOR KINASE1 ( At BAK1) in the PM. Here, we report that in contrast to At EPS1, the TGN/EE-localized At MTV1 did not contribute significantly to immunity against pathogenic Pto DC3000 bacteria. We also compared the amino acid sequences, peptide motif structures and in silico tertiary structures of the ENTH domains of At EPS1 and At MTV1 in more detail. We conclude that despite sharing the classical tertiary alpha helical ENTH-domain structure and clathrin-binding motifs, the overall low amino acid identity and differences in peptide motifs may explain their role(s) in trafficking of some of the same as well as distinct cargo components to their site of function, with the latter potentially contributing to differences in physiological responses.